Production, Nutrient Utilization and Profitability of African Catfish (Clarias gariepinus, Burchell, 1822) Fed with Different Feed Types and Reared Under Two Production Systems: Production of African catfish in two culture systems - Sulem Yong, Nina Nindum; Junie Wandji Tchakoute; Christelle Sorelle Nanda Nganso; Etouke Essoh, Adrien M.; Yong-Sulem, Steve; Agbor Etchu, Kingsley; Nola, Moïse; Serge Hubert Togouet Zebaze (Journal of Aquaculture and Fish Health, 2025)
Growth performance, survival, nutrient utilization, body composition and profitability of Clarias gariepinus fed with imported extruded (Le), locally pelleted (Lpe) and locally extruded (Lex) feeds and reared under two production facilities was investigated. The study was conducted in nine IBC tanks and nine net hapas in installed in a 500m2 earthen pond with holding water capacity ranging from 0.8 to 0.9 m3. For each system, 900 juveniles of mean initial weight ranging from 10.68 ± 4.93 g to 15.15 ± 3.48 g were stocked at 100 juveniles holding system-1 and were fed thrice a day for 16 weeks. Final mean weights for tank system were respectively ranged from 758.46 ± 13.79g, 289.03 ± 60.67g and 339.27 ± 9.34g for Le, Lpe and Lex feeds. As for hapas-in-pond system, final mean weights were 726.02 ± 82.91g, 396.85 ± 18.96g and 461.73±13.26g respectively for Le, Lpe and Lex feeds. Fish fed with “Le” exhibited significantly higher growth performance and better nutrient utilisation (p<0.05) irrespective of the production system. However, fish fed “Lpe” and “Lex” feeds exhibited higher (p<0.05) growth performances in hapas-in-pond system. The economic assessment revealed that the use of “Le” feeds to feed African catfish was economically efficient as indicated by the lower incidence cost and higher profit when compared to the local feeds. The fact that the studied feeds were profitable as indicated by the benefit cost ratio >1 irrespective of the production system proves that if the ingredients used to formulate the local feeds are correctly formulated and blended properly, these feeds can provide similar growth rates, survival and yields of African catfish similar to imported feeds.